KAJIAN POLA RUANG DAN LITURGI DALAM GEREJA KATOLIK - Daeli, Fransiskus Fonnie; Silitonga, Shanty (Unika Santo Thomas, 2023)
The Catholic Church has certain spatial patterns, these patterns are formed due to several things, one of which is the liturgical process. The liturgical process in Catholicism is divided into five stages, each process will have a need for certain spaces. Apart from that, all of these liturgical processes have their own provisions which influence each other. This research will examine the relationship and pattern of space that is created as a result of the relationship between these two things. The research method used is qualitative with descriptive data processing. There are two Catholic churches used as the object of study, namely Gereja Katolik Santa Maria Tak Bernoda Asal (Katedral) and Gereja Santa Maria Ratu Rosari. This study found that the spatial patterns in the two church samples show a clear relationship with the liturgical process which is a core part of Catholic religious rituals.